Psycho-Social Factors Contributing to Marriage Proposal Rejection among Pakistani Men and Women: A Phenomenological Study - Rasheed , Salma; Zafar , Areeza; Sultana , Zoya; Saeeed , Iqra (Al-Qanṭara, 2025)
This qualitative research explore the experiences and psycho-social factors of marriage proposal rejection among Pakistani men and women. Adopting a phenomenological approach, the study seeks to elucidate the lived experiences of those who have experienced proposal rejection. The main research question examined was: What are the psycho-social factors of marriage proposal rejection? Six participants (Three male, Three female) who were previously rejected in their marriage proposals were selected through purposive sampling. Data were gathered using in-depth interviews, with an interview protocol being derived from the available literature. The research utilized the Interpretative Phenomenological Analysis (IPA), which is concerned with people's subjective experiences and how they make sense of them. Through the analytical steps of Smith et al. (2012), data analysis produced 10 themes, 4 of which were superordinate themes: social standards, concerns, psychological factors for proposal rejection, and coping mechanisms employed to deal with rejection. Further, 26 sub-themes were produced for the male participant and 22 for the female participant. The results point towards societal expectations, individual and family concerns, psychological effects, and coping mechanisms related to marriage proposal rejection. This research presents meaningful information on the dominant societal norms underpinning marriage proposal acceptance and rejection, with implications for psychological counseling, social awareness, and subsequent studies on marital decision-making in Pakistan.